2004
DOI: 10.1002/cyto.a.20070
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent CXCL12AF647 as a novel probe for nonradioactive CXCL12/CXCR4 cellular interaction studies

Abstract: BackgroundChemokines drive the migration of leukocytes via interaction with specific G protein–coupled 7‐transmembrane receptors. The chemokine ligand/receptor pair stromal cell–derived factor‐1 (SDF‐1, CXCL12)/CXCR4 is gaining increasing interest because of its involvement in the metastasis of several types of cancer and in certain inflammatory autoimmune disorders such as rheumatoid arthritis. In addition, CXCR4 serves as an important coreceptor for cellular entry of T‐tropic strains of human immunodeficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…Similarly, using a fluorescent antagonist for the prostanoid EP 3 R, it was shown that the EP 3 R was expressed in murine kidney and in human brain tissue (Tomasch et al, 2012a). In T lymphocytes, a CXCL12 based fluorescent ligand has been used in conjunction with both microscopy and flow cytometry to identify CXCR4 positive Tlymphoid SupT1 cells (Hatse et al, 2004) and expression of the CB2 receptor on CD4þ T cells was demonstrated using a fluorescent ligand for the cannabinoid CB2 receptor (Petrov et al, 2011). For the neuropeptide Y 1 receptor (Y 1 R), the development of a small molecule fluorescent antagonist allow the confirmation of the expression of the receptor in a human breast cancer cell line (MCF-7) and interestingly using flow cytometry they showed that they could measure the affinity of unlabelled antagonists in a erytholeukemia cell line that endogenously expresses the Y 1 R (Schneider et al, 2007).…”
Section: Use Of Fluorescent Ligands In Endogenous Systemsmentioning
confidence: 98%
“…Similarly, using a fluorescent antagonist for the prostanoid EP 3 R, it was shown that the EP 3 R was expressed in murine kidney and in human brain tissue (Tomasch et al, 2012a). In T lymphocytes, a CXCL12 based fluorescent ligand has been used in conjunction with both microscopy and flow cytometry to identify CXCR4 positive Tlymphoid SupT1 cells (Hatse et al, 2004) and expression of the CB2 receptor on CD4þ T cells was demonstrated using a fluorescent ligand for the cannabinoid CB2 receptor (Petrov et al, 2011). For the neuropeptide Y 1 receptor (Y 1 R), the development of a small molecule fluorescent antagonist allow the confirmation of the expression of the receptor in a human breast cancer cell line (MCF-7) and interestingly using flow cytometry they showed that they could measure the affinity of unlabelled antagonists in a erytholeukemia cell line that endogenously expresses the Y 1 R (Schneider et al, 2007).…”
Section: Use Of Fluorescent Ligands In Endogenous Systemsmentioning
confidence: 98%
“…Competition for CXCL12 AF647 binding was measured on CXCR4-or CXCR7-transfected CHO cells as described previously (36). Briefly, 1.5 ϫ 10 6 cells/ml (300,000 cells in 200 l) were incubated for 1 h at 4°C with 20 ng/ml CXCL12 AF647 and varying concentrations of unlabeled chemokine in RPMI 1640 plus 2% FBS.…”
Section: Binding Studiesmentioning
confidence: 99%
“…16,21 By using Alexafluor-647-coupled CXCL12 (CXCL12 AF647 ), a fully functional and specific CXCL12 chemokine derivative, 24,25 we showed that CXCL12 AF647 could bind to CD34 1 HSPCs (n 5 4, Figure 2A). …”
mentioning
confidence: 99%